1994
DOI: 10.1002/j.1460-2075.1994.tb06838.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel pattern of editing regions in mitochondrial transcripts of the cryptobiid Trypanoplasma borreli.

Abstract: In mitochondria of Kinetoplastida belonging to the suborder Trypanosomatina, the nucleotide sequence of transcripts is post‐transcriptionally edited via insertion and deletion of uridylate residues. In order to shed more light on the evolutionary history of this process we have searched for editing in mitochondrial RNAs of Trypanoplasma borreli, an organism belonging to the suborder Bodonina. We have cloned and sequenced a 5.3 kb fragment derived from a 37 kb mitochondrial DNA molecule which does not appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 68 publications
4
58
1
Order By: Relevance
“…Phylogeny of kinetoplastid minicircles and minicircle networks+ The phylogenetic tree was constructed as described in Materials and Methods, based on the nucleotide and amino acid sequence of a 296 nt cox2 (c)DNA fragment+ The occurrence of kinetoplast DNA networks and gRNAs has been listed, the question mark indicating that the existence of gRNAs has not been formally proved for C. helicis+ The size of the (presumed) gRNA-encoding (mini)circles has been indicated in the right column [*, depending on the strain: 10 kb in strain A1412 and 5+9 kb in strain A493 (Yurchenko et al+, 1999)]+ The significance of the different types of arrows is discussed in the text+ amounts would be released as dimers and trimers+ For other possible linkage numbers (n ϭ 4, n ϭ 6), the number of released monomeric circles predicted to arise would be virtually zero+ Because our preparations contained 55-75% circular monomers, we conclude that the absence of a kDNA network in B. saltans (mt)DNA is not due to its degradation during DNA isolation, but rather to the fact that the minicircles are not organized in a network+ The reason for the existence of minicircle dimers and trimers is unclear+ However, one should realize that comparable amounts of dimers and trimers of circular mt DNAs are also found in mitochondria of mammalian cells, in which they are likely to be (side) products of DNA replication or recombination (Clayton et al+, 1968)+ The mt genetic system of the bodonid B. saltans resembles that of trypanosomatids with respect to maxicircle gene organization, editing patterns of mt mRNAs, and the existence of gRNA-containing minicircles (see Blom et al+, 1998a)+ However, as far as the organization of the kDNA is concerned, B. saltans mt DNA is more similar to other bodonids such as B. caudatus (Hajduk et al+, 1986) and the cryptobiids C. helicis (Lukes et al+, 1998) and T. borreli (Lukes et al+, 1994;Yasuhira & Simpson, 1996)+ In all these species the typical kDNA disc and the catenated kDNA network appear to be missing+ In T. borreli, minicircles are missing altogether and the gRNAs seem to reside on a (single?) 180-kb large circular DNA molecule (Yasuhira & Simpson, 1996)+ In B. caudatus and C. helicis, noncatenated minicircle-like circular DNAs of 10 and 12 (Hajduk et al+, 1986) and 4+2 kb (Lukes et al+, 1998) have been found, but it remains to be demonstrated that these molecules indeed contain gRNA genes+ This makes B. saltans the first organism shown to possess gRNA-containing, noncatenated minicircles (see Fig+ 7)+ It has been proposed that the function of the kDNA network in trypanosomatid flagellates is to prevent the loss of essential minicircle-encoded gRNA genes during kDNA replication (Borst, 1991)+ Although this may be true for trypanosomatids, B. saltans seems to get by perfectly without a network and it remains to be established how the loss of essential minicircles is prevented in this organism+ Possible scenarios could be minicircle redundancy, as proposed for C. helicis, which appears to harbor three times as many (putative) minicircles as C. fasciculata …”
Section: B Saltans Minicircles Are Not Organized In Large Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogeny of kinetoplastid minicircles and minicircle networks+ The phylogenetic tree was constructed as described in Materials and Methods, based on the nucleotide and amino acid sequence of a 296 nt cox2 (c)DNA fragment+ The occurrence of kinetoplast DNA networks and gRNAs has been listed, the question mark indicating that the existence of gRNAs has not been formally proved for C. helicis+ The size of the (presumed) gRNA-encoding (mini)circles has been indicated in the right column [*, depending on the strain: 10 kb in strain A1412 and 5+9 kb in strain A493 (Yurchenko et al+, 1999)]+ The significance of the different types of arrows is discussed in the text+ amounts would be released as dimers and trimers+ For other possible linkage numbers (n ϭ 4, n ϭ 6), the number of released monomeric circles predicted to arise would be virtually zero+ Because our preparations contained 55-75% circular monomers, we conclude that the absence of a kDNA network in B. saltans (mt)DNA is not due to its degradation during DNA isolation, but rather to the fact that the minicircles are not organized in a network+ The reason for the existence of minicircle dimers and trimers is unclear+ However, one should realize that comparable amounts of dimers and trimers of circular mt DNAs are also found in mitochondria of mammalian cells, in which they are likely to be (side) products of DNA replication or recombination (Clayton et al+, 1968)+ The mt genetic system of the bodonid B. saltans resembles that of trypanosomatids with respect to maxicircle gene organization, editing patterns of mt mRNAs, and the existence of gRNA-containing minicircles (see Blom et al+, 1998a)+ However, as far as the organization of the kDNA is concerned, B. saltans mt DNA is more similar to other bodonids such as B. caudatus (Hajduk et al+, 1986) and the cryptobiids C. helicis (Lukes et al+, 1998) and T. borreli (Lukes et al+, 1994;Yasuhira & Simpson, 1996)+ In all these species the typical kDNA disc and the catenated kDNA network appear to be missing+ In T. borreli, minicircles are missing altogether and the gRNAs seem to reside on a (single?) 180-kb large circular DNA molecule (Yasuhira & Simpson, 1996)+ In B. caudatus and C. helicis, noncatenated minicircle-like circular DNAs of 10 and 12 (Hajduk et al+, 1986) and 4+2 kb (Lukes et al+, 1998) have been found, but it remains to be demonstrated that these molecules indeed contain gRNA genes+ This makes B. saltans the first organism shown to possess gRNA-containing, noncatenated minicircles (see Fig+ 7)+ It has been proposed that the function of the kDNA network in trypanosomatid flagellates is to prevent the loss of essential minicircle-encoded gRNA genes during kDNA replication (Borst, 1991)+ Although this may be true for trypanosomatids, B. saltans seems to get by perfectly without a network and it remains to be established how the loss of essential minicircles is prevented in this organism+ Possible scenarios could be minicircle redundancy, as proposed for C. helicis, which appears to harbor three times as many (putative) minicircles as C. fasciculata …”
Section: B Saltans Minicircles Are Not Organized In Large Networkmentioning
confidence: 99%
“…DNA from B. saltans and C. fasciculata was spread for electron microscopy as described (Lukes et al+, 1994), using bacteriophage PM2 DNA (Boehringer) as an internal size marker+ Spread DNA was stained in 10 Ϫ5 M uranyl acetate for 10 s, rinsed in 90% ethanol, and air-dried+ After rotary shadowing with platinum/palladium at an angle of 78, grids were viewed in a Philips EM 400+ A grating replica was used to determine the magnification+…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…As the bodonid species Trypanoplasma borreli has U-insertion/deletion type editing, the process is at least 500 -700 million years old (10,11). The flagellates (kinetoplastids, diplonemids and euglenoids) form one of the earliest diverging eukaryotic lineages having mitochondria (12).…”
Section: Introductionmentioning
confidence: 99%
“…The alignment with the C. fasciculata mitochondrial topo II (22) (genomic sequence is available only for one mitochondrial topo II), and other available trypanosomatid topo II genes revealed a level of identity similar to that observed in other bodonid versus trypanosomatid gene alignments (17,28). We have identified neither a mitochondrial targeting signal nor a cycling element that confers cycling to topo II in C. fasciculata (23).…”
Section: Discussionmentioning
confidence: 63%